Combined Rosiglitazone and Forskolin Have Neuroprotective Effects in SD Rats after Spinal Cord Injury. (21st June 2018) - Meng, Qing-qi; Lei, Wei; Chen, Hao; Feng, Zhen-cheng; Hu, Li-qiong; Zhang, Xing-liang; Li, Siming
Abstract : The peroxisome proliferator-activated receptor gamma (PPAR- γ ) agonist rosiglitazone inhibits NF- κ B expression and endogenous neural stem cell differentiation into neurons and reduces the inflammatory cascade after spinal cord injury (SCI). The aim of this study was to explore the mechanisms underlying rosiglitazone-mediated neuroprotective effects and regulation of the balance between the inflammatory cascade and generation of endogenous spinal cord neurons by using a spinal cord-derived neural stem cell culture system as well as SD rat SCI model. Activation of PPAR- γ could promote neural stem cell proliferation and inhibit PKA expression and neuronal formation in vitro. In the SD rat SCI model, the rosiglitazone + forskolin group showed better locomotor recovery compared to the rosiglitazone and forskolin groups. MAP2 expression was higher in the rosiglitazone + forskolin group than in the rosiglitazone group, NF- κ B expression was lower in the rosiglitazone + forskolin group than in the forskolin group, and NeuN expression was higher in the rosiglitazone + forskolin group than in the forskolin group. PPAR- γ activation likely inhibits NF- κ B, thereby reducing the inflammatory cascade, and PKA activation likely promotes neuronal cell regeneration.